Problems of the implementation of energy-saving technologies in heat supply - E. Kamchatova; R. Voronin (Вестник университета, 2016)
The article discusses a number of problems associated with the introduction of energy saving technologies in heat supply organizations. It characterizes the current state of the legal framework in the field of the energy saving in heat supply; observed trends in the implementation of energy efficiency programs in the district heating companies; a program of energy conservation and energy efficiency of Russia until 2020 was analyzed. On the basis of a comprehensive analysis of a number of heat suppliers, authors reveal the typical problems of the introduction of energy saving technologies.